Pengaruh Brand Awareness, Brand Image, dan Kualitas Produk terhadap Keputusan Pembelian Mobil Suzuki di Batam - Gabriel Hadinata; Tiurniari Purba (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the influence of Brand Awareness, Brand Image, and Product Quality on purchasing decisions for Suzuki cars in Batam City. The research applies a quantitative approach using a survey method by distributing structured questionnaires to respondents. The sampling technique employed is simple random sampling, involving 100 respondents who have previously purchased Suzuki cars in Batam, without limitations related to age or gender. The collected data were processed and analyzed using statistical techniques to determine the relationships and levels of influence among the research variables. The findings reveal that Brand Awareness, Brand Image, and Product Quality each have a positive and statistically significant effect on consumers’ purchasing decisions. These results indicate that stronger brand recognition, favorable brand perception, and higher perceived product quality contribute substantially to increasing consumers’ intention and confidence in purchasing Suzuki vehicles. Consequently, companies are encouraged to strengthen brand promotion strategies, maintain a positive brand reputation, and consistently improve product quality to enhance competitiveness and attract more potential consumers in the automotive market.